The criteria of the goodness and ugliness in God’s action in the view Fakhr al-Din al- Razi: Criticizing of the epistemological separation of the God and Human’ ethics - mahmood seyedi; seyed mostafa mosavi aezam; hasan akhtar (اخلاق وحیانی)
Abstract In the view of Fakhr al-Din al- Razi, the criteria of the goodness or ugliness of human actions is reason but this is not true about the God’s actions and the criteria in this case is Sharia Law. Reason comprehends the pleasant or unpleasant of actions in the human nature but it can’t comprehend these things about the reward or torment. In spite of Razi’s efforts in the articulation of his view, this distinction between human and God’s action about the goodness or ugliness is not true and human reason can comprehend these two kinds of action without any differences. God’s action, Sharia’s Law (for example God’s enjoining and forbidding to the unbelievers), and multiplicity of rational soul faculties have reasonable end. Also, by disproving the determinism, man can select between different kinds of action in the regard of goodness or ugliness of actions. Key words; Razi, Goodness, Ugliness, Reason, God, Law.